2010
DOI: 10.1074/jbc.m109.052068
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Glycoprotein P2 (Rhp2) Is a Novel Member of the Rh Family of Ammonia Transporters Highly Expressed in Shark Kidney

Abstract: Functional analysis using the Xenopus oocyte expression system showed that Rhp2 has transport activity for methylammonium, an analog of ammonia. This transport activity was inhibited by NH 4 Cl but not trimethylamine-N-oxide and urea. These results suggested that Rhp2 is involved in ammonia reabsorption in the kidney of the elasmobranch group of cartilaginous fish comprising the sharks and rays.Members of the Rhesus (Rh) 4 glycoprotein family are membrane proteins present in a broad range of eukaryotes includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 58 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…Finally, in the year 2000, Marini and co-workers discovered that members of the Rhesus protein family, when expressed in yeast are able to mediate ammonia transport (Marini et al, 2000). Subsequent functional expression analysis showed that the glycosylated members of the Rh protein family (Rhag, Rhbg, Rhcg) from mammals and fish are functional ammonia transporters (Ludewig, 2004;Mak et al, 2006;Marini et al, 2000;Nakada et al, 2010;Nawata et al, 2010a,b;Zidi-Yahiaoui et al, 2005). For the human Rh protein RhCG, an X-ray crystallographic structure analysis revealed that this transporter forms a trimeric complex and each monomer promotes the passage of NH 3 (Gruswitz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in the year 2000, Marini and co-workers discovered that members of the Rhesus protein family, when expressed in yeast are able to mediate ammonia transport (Marini et al, 2000). Subsequent functional expression analysis showed that the glycosylated members of the Rh protein family (Rhag, Rhbg, Rhcg) from mammals and fish are functional ammonia transporters (Ludewig, 2004;Mak et al, 2006;Marini et al, 2000;Nakada et al, 2010;Nawata et al, 2010a,b;Zidi-Yahiaoui et al, 2005). For the human Rh protein RhCG, an X-ray crystallographic structure analysis revealed that this transporter forms a trimeric complex and each monomer promotes the passage of NH 3 (Gruswitz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In elasmobranchs, there are only two previous reports of Rh proteins -Rhbg in the intestine, rectal gland and kidney (the only tissues examined) of the little skate, Leucoraja erinacea (Anderson et al, 2010), and Rhp2 in the kidney of the houndshark, T. scyllium (Nakada et al, 2010). In contrast to the present findings, Nakada et al (Nakada et al, 2010) reported that Rhp2 was present only in the kidney, but this conclusion was based on northern blot screening, which is less sensitive than the qPCR employed here. As branchial Rhp2 expression did not respond to HEA exposure (Fig.…”
mentioning
confidence: 99%
“…This result suggests that the two molecules share a common transport system, and is again consistent with a mechanism mediated by Rh proteins. For trout Rh proteins expressed in oocytes, concentrations of ammonia approximately 2-fold greater than those used here are needed to achieve 50% inhibition of [ 14 C]MA uptake (Nawata et al, 2010a), and in the only comparable study on an elasmobranch Rh protein, a 10-fold higher concentration was needed to cause 100% inhibition (Nakada et al, 2010). In our experiments, we wished to avoid such high concentrations as they would probably have been fatal to the intact animal.…”
Section: Environmental and Physiological Relevance Of Branchial Ammonmentioning
confidence: 99%
“…Together with basolaterally located V-type H + -ATPase (Tresguerres et al, 2005(Tresguerres et al, , 2006, these Rh proteins could function as a metabolon to pump ammonia-N from gill cells to blood, analogous to the apical Rhcg metabolon that pumps ammonia-N from gill cells to the external water in teleosts (Wright andWood, 2009, 2012). In the kidney of another elasmobranch, Triakis scyllium, Nakada et al (2010) have similarly proposed that basolateral Rhp2 serves to recover ammonia-N from the urine. Unfortunately, as yet, there are no pharmacological blockers of Rh proteins to test these ideas.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation